(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The anime series and films have achieved wide success and fame at the level of cinematic and television works, and their presence has been overwhelming in recent years, as this type of artistic work witnessed tremendous developments at all levels, which led to the production of anime works that competed with fictional works and achieved wide fame and reaped a lot of reviews. international awards, and that this success would not have been achieved if there were no active and influential forces within the structure of the artwork, as through the active forces the maker of the work can communicate his idea and message to the public, as it becomes the basis around which the work is built, and the importance of the active forces within the structure of the work The importance of the research, through which the researcher will address the issue of the active forces in anime series and movies, and the research is divided into four chapters as follows:.The first chapter (methodical framework) included the research problem, which was represented by the following question: What are the active forces in anime films?Hence the importance of the research and its objectives, as well as the limits of the research.The second chapter (theoretical framework) was divided into three sections:The first topic (the concept of active forces)The second topic (the formal structure of the active forces)The third topic (the active forces in anime series and films)The third chapter (research procedures) included:The research methodology, where the researcher adopted the descriptive approach and the research sample, which was represented in the movie (A Home in the Heart of the Ocean), which was chosen as an intentional sample that is compatible with the subject and unit of analysis, the analysis tool, and finally the sample analysis.As for the fourth chapter (results and conclusions), it included the results of the research that the researcher reached, the most important of which are1- The active forces are distinguished by their basic characteristics that made them a real actor, whether on the narrative, semantic or aesthetic level.2- The external form of the active forces departs from what is traditional.3- Formal structures have an important and essential presence in creating the active forces in the analysis models that have been chosen.As well as the conclusions drawn by the researcher in the light of the research results.Keywords: active forces - anime films - anime series. the anime